Chemical‐Bonding‐Directed Hierarchical Assembly of Nanoribbon‐Shaped Nanocomposites of Gold Nanorods and Poly(3‐hexylthiophene). Issue 30 (17th May 2016) - Pan, Shuang; He, Luze; Peng, Juan; Qiu, Feng; Lin, Zhiqun
Abstract: Nanoribbon‐shaped nanocomposites composed of conjugated polymer poly(3‐hexylthiophene) (P3HT) nanoribbons and plasmonic gold nanorods (AuNRs) were crafted by a co‐assembly of thiol‐terminated P3HT (P3HT‐SH) nanofibers with dodecanethiol‐coated AuNRs (AuNRs‐DDT). First, P3HT‐SH nanofibers were formed due to interchain π–π stacking. Upon the addition of AuNRs‐DDT, P3HT‐SH nanofibers were transformed into nanoribbons decorated with the aligned AuNRs on the surface (i.e., nanoribbon‐like P3HT/AuNRs nanocomposites). Depending on the surface coverage of the P3HT nanoribbons by AuNRs, these hierarchically assembled nanocomposites exhibited broadened and red‐shifted absorption bands of AuNRs in nIR region due to the plasmon coupling of adjacent aligned AuNRs and displayed quenched photoluminescence of P3HT. Such conjugated polymer/plasmonic nanorod nanocomposites may find applications in fields, such as building blocks for complex superstructures, optical biosensors, and optoelectronic devices. Abstract : Turning fibers into ribbons : Nanoribbon‐shaped nanocomposites composed of a conjugated polymer, poly(3‐hexylthiophene) (P3HT), and plasmonic gold nanorods (AuNRs) are produced by a co‐assembly of thiol‐terminated P3HT nanofibers with dodecanethiol‐coated AuNRs. Owing to plasmon coupling between adjacent aligned AuNRs, these nanocomposites show broadened and red‐shifted absorption bands.